Characteristics and conditions for ignition of bio-coal mixtures based on coal and forest combustible material; Journal of the Energy Institute; Vol. 93, iss. 5 - Syrodoy S. V. Semen Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Gutareva N. Yu. Nadezhda Yurievna; Kostoreva Zh. A. Zhanna Andreevna; Kostoreva A. A. Anastasiya Andreevna; Nigay N. A. Nataljya Andreevna (2020, 2020)
Title screen